Yemen and the New Regional Order - Sławek, Jakub (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
This article intends to shed light on the political and security developments in Yemen that ultimately resulted in the Saudi-led military operation in this country. It discusses the political background behind the Yemeni revolution of 2011, its positive outcome in the shape of the results of the National Dialogue Conference and the reasons for the collapse of the efforts to stabilize Yemen.